Reduced cytotoxicity and boosted antibacterial activity of a hydrophilic nano-architecture magnetic nitrogen-rich copper-based MOF. (December 2022) - Asgari, Shadi; Mohammadi Ziarani, Ghodsi; Badiei, Alireza; Rostami, Mojtaba; Kiani, Mahsa
Abstract: A new category of antibacterial compounds is copper-based metal-organic frameworks which suffer from cytotoxicity caused by the fast release of copper ions and low hydrophilicity. Their post-synthetic modification with nitrogen-rich dendrimers is suggested to resolve the problems. We synthesized a magnetic nitrogen-rich N-doped copper-based metal-organic framework as a post-synthetically modified metal-organic framework through four steps:1) synthesize the third generation of magnetic polyamidoamine dendrimer containing the core of iron oxide nanoparticles and amine branches, 2) synthesize N-doped copper-based metal-organic framework through polyvinylpyrrolidone-assisted strategy, 3) modification of the framework with L -cysteine, and 4) post-synthetic modification of L -cysteine modified metal-organic framework by as-prepared magnetic dendrimer. All of the synthesis steps were studied with Powder X-ray diffraction, Fourier-transform infrared spectroscopy, zeta-potential, ultraviolet-visible spectroscopy, field emission scanning electron microscopy/energy-dispersive X-ray spectroscopy, and CHNS elemental analysis. The water contact angles of 60 o for N-doped copper-based metal-organic framework, 38 o for L -cysteine modified metal-organic framework, and 35 o for the framework which was modified with both L -cysteine and dendrimer confirmed increasing hydrophilicity of the metal-organic framework after the post-synthetic modifications. Reduced cytotoxicity (57.5% of cell viability within 24 h), controlled release of copper ions (1.7 µg. mL -1 within 96 h), and boosted antibacterial activity (inhibition zone diameter of 11 mm on E. coli and 14 mm on S. aureus ) were observed for the N-doped copper-based metal-organic framework modified with both L -cysteine and magnetic dendrimer compared to the N-doped copper-based metal-organic framework that was only modified with L -cysteine which can be attributed to the presence of nitrogen-rich dendrimer. Graphical Abstract: ga1 Highlights: Post-synthetic modification of N-Cu-MOF by L -cysteine and MNP@PAMAM. A magnetic nitrogen-rich N-Cu-MOF with increased hydrophilicity. Reduced cytotoxicity, controlled release of Cu ions, and boosted antibacterial activity.